Program Aktivitas Fisik sebagai Strategi Kesejahteraan Karyawan di Rumah Sakit : Tinjauan Sistematis - Purnomo, Jeki; Haeril, Haeril (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Pamane Talino, 2025)
Healthcare worker wellbeing has become a strategic priority in modern healthcare systems where high work pressure, occupational stress and burnout risks threaten healthcare service quality. Physical activity programs have been recognized as effective interventions for improving worker health, yet systematic evaluation of their implementation in healthcare institutions remains limited. This study aims to systematically analyze the effectiveness of physical activity programs as organizational wellness strategies in hospitals and their impact on organizational performance indicators. Methods: A systematic review was conducted following PRISMA protocol with comprehensive searches in PubMed, Scopus, Web of Science, Google Scholar and SINTA databases from 2020-2025. Inclusion criteria comprised empirical studies evaluating physical activity programs in healthcare institutions measuring impact on employee wellbeing or organizational indicators. 47 studies met inclusion criteria with 89,460 total participants. Multimodal programs (47% of studies) with 12-24 week duration demonstrated high effectiveness. A total of 81.3% of studies reported significant increases in physical activity levels (standardized mean difference +0.25) and 80% showed psychological stress reduction (Cohen's d = -0.42). Supervised workplace-based programs yielded superior adherence (67%) compared to individual programs (33%). Organizational impacts included 1.8 fewer sick days per year per employee (OR = 0.67), improved Work Ability Index (66.7% of studies), and return on investment of 3.27 per 1 invested. Conclusion: Physical activity programs prove effective as organizational wellness strategies with measurable impacts on individual health and organizational performance indicators. Optimal implementation requires multimodal approaches, supervised sessions, management support, and protected time during work hours